Bills as daggers? A test for sexually dimorphic weapons in a lekking hummingbird. (18th October 2014) - Rico-Guevara, Alejandro; Araya-Salas, Marcelo
Abstract : One way in which secondary sexual traits can influence differential reproductive success is by playing a key role in the outcome of direct physical contests for mates. Here we describe an undocumented trait in a species of hummingbird with a lek mating system, the Long-billed hermit (LBH, Phaethornis longirostris ). The trait under consideration is a dagger-like structure at the bill tip, which we hypothesize is a secondary sexual trait that functions as a sexually dimorphic weapon. We tested our hypothesis by examining 5 leks during 4 consecutive years, and by employing morphological analyses, performance experiments, and behavioral observations. We found that 1) adult male bill tips were longer and pointier than their counterparts in females and juvenile males, 2) juvenile males acquired dagger-like tips during their transition to adulthood, 3) variation in bill tip morphology reflected puncture capability, and 4) males with larger and pointier bill tips were more successful in achieving lek territory tenure. Our study provides the first evidence of sexually dimorphic weapons in bird bills and stands as one of the few examples of male weaponry in birds. Our results suggest a role of sexual selection on the evolution of overall bill morphology, an alternative hypothesis to the prevailing "ecological causation" explanation for bill sexual dimorphism in hummingbirds. Lay Summary: We found novel differences in the bills of female and male hummingbirds, and show that these differences are related to the males' ability to defend territories necessary to attract females. Our findings contradict the traditional explanation that the differences in bill shape between the sexes are caused by differential feeding at dissimilar flower shapes. We provide the first evidence of weapons in bills and one of the few examples of male weaponry in birds.